Just-in-Time Leadership Seminars for Chairs - Edwin Rousculp; Curt Guaglianone; Mary James; Charles Wheaton (Academic Chairpersons Conference Proceedings, 2016)
Just-in-time chair seminars keyed to annual calendar of chair responsibilities provided ample opportunities for chair questions, sharing of strategies, challenges, and problem solving. Participation of chairs across disciplines and the intentional inclusion of student services administrators created opportunities for transformative dialogue and the emergence of new pathways to systemic effectiveness.
Keywords: Academic Leadership; Cross-Campus Collaboration; Departmental Culture; Learning Communities; Systemic Effectiveness